A bi-layered tubular scaffold for effective anti-coagulant in vascular tissue engineering. (September 2020) - Yao, Wangchao; Gu, Hongbing; Hong, Tao; Wang, Yao; Chen, Sihao; Mo, Xiumei; Li, Wenyao; Wang, Chunsheng; Zhu, Tonghe; Lu, Shuyang
Abstract: Acute coagulation is one of the vexed problems in transplantation of small-diameter artificial blood vessel. Three-dimensional porous heparin-modified gelatin (Gel)@chitosan (CS) tubular scaffold were successfully acquired by using the method of freeze-drying combined with amination for application in tissue regeneration of blood vessels. Initially, homogeneous gelatin solution was initially poured into a tubular mold and underwent a procedure of vacuum freeze-drying to form a three-dimensional porous tubular skeleton. Chitosan was used to loading heparin (Hep) which is a kind of efficient anticoagulant. The Hep-loaded CS composite solution were poured into Gel tubular skeleton, following freeze-drying matched EDC-NHS crosslinking to form Gel@CS-Hep tubular scaffold exhibited a three-dimensional structure and porous morphology. Then, poly(ester-urethane)urea/gelatin (PU75) micro-nano fibers were electrospinning outside the Gel@CS-Hep tube as mechanical reinforcement layer. The Gel@CS-Hep/PU75 tube showed higher hydrophilicity, stable mechanical properties as well as no cytotoxicity on human umbilical vein endothelial cells. Importantly, the three-dimensional functional Gel@CS-Hep/PU75 tubular scaffold shows a good rapid endothelialization performance and effective anti-acute coagulation properties. Therefore, the developed Gel@CS-Hep/PU75 tube was proposed to be a potential scaffold for remodeling vascular tissue. Graphical abstract: A hybrid bi-layered vascular scaffold from heparin-grafted gelatin (Gel) and chitosan (CS) composite sponge with porous fluffy inter structure exhibited higher hydrophilicity, stable mechanical properties, especially they demonstrate excellent rapid endothelialization performance and effective anti-acute coagulation properties in rabbit carotid artery model. Unlabelled Image Highlights: A hybrid bi-layered tubular scaffold were fabricated via a facile freeze-drying combined with amidation. The mechanically matched scaffold showed no unfavorable effects on vascular cells and effective anti-acute coagulation properties. A novel designed bi-layered vessel prevents acute thrombosis effectively and maintains excellent patency in a rabbit model.